A Simplified Approach of Pumping Rate Optimization for Production Wells to Mitigate Saltwater Intrusion: A Case Study in Vinh Hung District, Long An Province, Vietnam - Pham Quy Nhan; Dang Tran Trung; Tran Thanh Le; Nguyen Kim Hung; Pham Minh Hoang; Tran Duc Thinh (Hydrology)
In the investigation of optimal groundwater extraction in coastal regions, conventional assumptions typically revolve around unconfined aquifers with specified boundary conditions. In such cases, intricate solutions for groundwater management have been documented. However, within extensive delta plains, the extraction wells are frequently drilled in confined aquifers with not much variable-density flow. This circumstance, characterized by paleo-saltwater intrusion, is further complicated by the placement of wells at a considerable distance from the coastal line. As a result, the design and implementation of groundwater supply systems in these areas necessitate strategic groundwater management to optimize groundwater utilization while mitigating the potential risk of saltwater intrusion. Analytical solutions and an optimization problem approach have been applied to address this challenge and solve the differential equations governing confined aquifers with salt–freshwater interfaces. These methodologies provide simplified yet dependable conditions tailored to the study area. A case study conducted in Vinh Hung district, Long An province, is focused on determining the optimal pumping rate for production wells to forestall saltwater intrusion during groundwater extraction. Here, the focus is on the migration of older saltwater towards inland pumped wells, rather than the influence of recent seawater encroachment. The findings contribute valuable insights into achieving an equilibrium between maximizing groundwater utilization and preventing saltwater intrusion in the aquifer systems by a simplified approach.